Interactive Uses of the IWB A Look at Quebec Teachers’ Practices - Gareau, Alexandre; Lefebvre, Sonia; Samson, Ghislain (Formation et profession, 2022)
In recent years, Quebec schools have experienced a technological renewal with the integration of digital tools, including interactive whiteboards (IWB) (MEES, 2018). Despite this digital upsurge, research shows that IWBs have received some criticism in the research, notably concerning the interactive aspect (Aflalo et al., 2018; Chen et al., 2020). This qualitative study describes various types of interactivity used with the IWB and the associated conditions. Results from discussions with 51 teachers reveal that the IWB is used primarily in traditional ways, and that few teachers attempt high-interactivity situations.